2016
DOI: 10.1002/chem.201601254
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the Copper to Late‐Transition‐Metal Transmetallation to Carbenes beyond N‐Heterocyclic Carbenes

Abstract: Carbene transition metal complexes have become a prevalent family of catalysts enabling numerous organic transformations. Their facile synthetic access is a matter of great importance. To this end, the Cu I -NHC transfer methodology has emerged as a powerful alternative presenting attractive advantages over other methods. Herein we report the remarkable ability of copper to not only transfer NHCs but also other types of carbene such as abnormal NHCs (aNHCs), cyclic (alkyl)(amino)carbenes (CAACs) and mesoionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 69 publications
(27 reference statements)
2
29
0
1
Order By: Relevance
“…To test the limits of the method, the mesoionic carbene (MIC) 7 case was examined using NEt 3 as base and, as suggested by the computed high‐energy barriers found along the reaction pathway, no product formation was observed after 20 hours at 60 °C (Scheme ). The weak‐base method does however lead to the desired metalated product ( 8 ) if K 2 CO 3 is employed . The exact role of K 2 CO 3 in the method is presently being investigated mechanistically, and appears to proceed through a pathway that permits the expansion of the ligand precursor‐type allowed under these initial NEt 3 conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the limits of the method, the mesoionic carbene (MIC) 7 case was examined using NEt 3 as base and, as suggested by the computed high‐energy barriers found along the reaction pathway, no product formation was observed after 20 hours at 60 °C (Scheme ). The weak‐base method does however lead to the desired metalated product ( 8 ) if K 2 CO 3 is employed . The exact role of K 2 CO 3 in the method is presently being investigated mechanistically, and appears to proceed through a pathway that permits the expansion of the ligand precursor‐type allowed under these initial NEt 3 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The weak-base methodd oes however lead to the desired metalatedp roduct (8)i fK 2 CO 3 is employed. [11,18] The exact role of K 2 CO 3 in the method is presently being investigated mechanistically,a nd appears to proceed through ap athway that permits the expansion of the ligand precursor-type allowed under these initial NEt 3 conditions. The identityo ft he weak base appears to have ap rofound influence on reaction outcome.…”
Section: Resultsmentioning
confidence: 99%
“…It is only recently that, in collaboration with the Cazin group, we found that heating a dioxane solution of iminium chloride 70 and Cu 2 O at 100 °C for 24 h allowed for the preparation of (CAAC)CuCl complexes (Scheme ) . Soon after, we showed that these copper complexes can efficiently transfer the CAAC ligand to other transition metals, such as Pd, Au, and Ir …”
Section: Coordination Chemistry Of Caacsmentioning
confidence: 96%
“…[139] Soon after, we showed that these copper complexes can efficiently transfer the CAAC ligand to other transition metals,s uch as Pd, Au,a nd Ir. [140] Waldmann et al showed that av ariety of chiral (CAA-C)AuCl complexes 72 are accessible through a( Me 2 S)AuCl triggered cyclization-rearrangement of 1,7-enyne substrates 71 (Scheme 22). [141] It should also be noted that this methodology gives access to al ibrary of CAAC derivatives that are not currently accessible through conventional methods.…”
Section: Coordination Chemistry Of Caacsmentioning
confidence: 99%
“…Wir konnten jedoch kürzlich in Kooperation mit dem Arbeitskreis Cazin zeigen, dass die Reaktion einer Dioxanlösung des Iminiumchlorids 70 mit Cu 2 O bei 100 °C nach 24 h die Isolierung des entsprechenden (CAAC)CuCl‐Komplexes ermöglicht (Schema ) . Die so erhaltenen Kupferkomplexe sind bestens geeignet, um den CAAC‐Liganden auf andere Übergangsmetalle wie Pd, Au und Ir zu übertragen …”
Section: Die Koordinationschemie Der Caacsunclassified